Conducta obstétrica en primigesta de 21 años de edad con embarazo de 37,6 semanas y síndrome de hellp. - Mera Ganchozo, Jennifer Karina (2021)
Hypertensive disorders of pregnancy are a group of complications whose connection is hypertension, they are classified according to their characteristics, which help us to differentiate them. HELLP Syndrome is a complication of pre-eclampsia-eclampsia; Present in pregnancy or postpartum, it consists of hemolysis, elevated transaminases, and decreased platelet count. Although its cause is not defined, it is associated with maternal endothelial damage. Its diagnosis is based on laboratory tests rather than on the appearance of symptoms because they are nonspecific and its main treatment is the termination of pregnancy. This syndrome is related to serious perinatal complications and increased maternal mortality. In the present clinical case, we have a 21-year-old primigravida with a pregnancy of +/- 37.6 weeks by date of the last menstruation, who attended a hospital of level II care, with a clinical picture characterized by pain in the upper right quadrant and hypogastrium. Accompanied by general malaise of +/- 2 days of evolution, I present at the moment breast score of 7 points. A toxemic profile was performed that was reported without alterations, the gynecologist on duty with a diagnosis of severe preeclampsia decided on pertinent treatment by termination of pregnancy via cesarean section, in the postoperative period she presented an alteration in the control laboratory tests and referred it as code red to a higher-level hospital diagnosed with HELLP Syndrome.